La motivación laboral y la gestión del talento humano del personal administrativo de la Unidad de Gestión Educativa Local de Requena, 2021 - Dominguez Rodriguez, Jheylym (2023)
For this study, the objective was to determine the relationship between motivation and human talent management of the administrative staff of the Local Educational Management Unit of Requena, year 2021, the level of quantitative research, descriptive and correlational type and non-experimental design, the population is made up of all the administrative workers of the UGEL of Requena, which in total are 30 people, a Pearson correlation value equal to 0.795** was obtained, which indicates a considerable positive correlation ( Hernandez, 2018) and according to the sigma value (bilateral) equal to 0.000, this correlation is significant. In addition, the workers perceive variable 1 Work motivation in the following way: 76.7% corresponding to 23 people considered that they have a "medium" level, 16.7% corresponding to 5 people a "high" level, and 6.7% corresponding to 2 people state that they have a “low” level; In the case of variable 2 Human talent management, 90.0% corresponding to 27 people considered that they have a "medium" level, 6.7% corresponding to 2 a "high" level, and 3.3% corresponding to 1 person states that they have a “low” level. It is concluded that the relationship between work motivation and the management of human talent of the administrative staff of the Local Educational Management Unit of Requena, year 2021, is significant.